Girlhood in Transition: Girls’ Shipboard Diaries on Journeys to New Zealand, 1879-1881 - Sautter, Lilja (Australasian Journal of Victorian Studies, 2013)
Nineteenth-century girlhood was imagined as a decisive period of liminality: distinct from both childhood and adulthood, it shaped the womanhood that followed it. Shipboard diaries written by emigrants engage with a similar period of transformation. Discussing three diaries written by girls en route from Scotland and Ireland to New Zealand, this essay explores how the liminality of girlhood and the liminality of the emigrant voyage are intertwined. While narrating a spatial and temporal transition, the three texts also negotiate a transformation in the concept of girlhood: the notion of the ideal colonial girl as brave, resourceful and hardworking developed traditional British expectations of women as responsible for the domestic sphere and as upholders of morals. Whereas two of the diarists stress qualities such as bravery, a sense of adventure, and good health, the third diarists focuses on a more traditional concept of girls as pure and virtuous. The texts’ adherence to and departures from the genre conventions of shipboard diaries emphasise the liminality of the journey, mirroring the transformative potential of new notions of girlhood.